2022
DOI: 10.3168/jdsc.2022-0290
|View full text |Cite
|
Sign up to set email alerts
|

A first time for everything: The influence of parity on the behavior of transition dairy cows

Abstract: Graphical Abstract Summary: The period from 3 wk before until 3 wk after calving is called the transition period. This is a challenging time for dairy cows due to the need to adapt, in a short period of time, to many physical and environmental changes, such as labor and delivery, the onset of lactation, pen changes, and new social groups. The primiparous cow experiences many of these changes for the very first time, and their responses to these changes differ from the older, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Previous studies have shown that lactation affects dairy cows’ behavioral activity patterns as calving approaches [ 16 , 46 , 47 ]. The present study’s findings are consistent with previous studies [ 12 , 48 ], which reported elevated activity as calving approaches in first-lactation dairy cows. Additionally, dairy cows in their second lactation and subsequent lactations (lactation No.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that lactation affects dairy cows’ behavioral activity patterns as calving approaches [ 16 , 46 , 47 ]. The present study’s findings are consistent with previous studies [ 12 , 48 ], which reported elevated activity as calving approaches in first-lactation dairy cows. Additionally, dairy cows in their second lactation and subsequent lactations (lactation No.…”
Section: Discussionsupporting
confidence: 93%
“…This association is statistically significant, illustrating distinct behavioral patterns across the lactation groups ( Table A1 ). Notably, first-lactation dairy cows exhibited the highest mean activity levels ( Table A1 ), possibly due to the combined stress of calving and adapting to a new lactating environment [ 12 , 44 ], which is further compounded by a lack of maternal experience [ 26 , 45 ]. Previous studies have shown that lactation affects dairy cows’ behavioral activity patterns as calving approaches [ 16 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in DMI of dairy cows could be attributed to different physiological stages of the cows (7). The DMI was not influenced by Cr supplementation in PP cows, which might be associated with greater stress in PP cows as compared to MP (48). The increase in DMI during BFP and AFP could be associated with a decrease in non-esterified fatty acids (NEFA) by Cr supplementation (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no statistical influence of the days in milk on the number of HHM and VHM or any other behavior. Previous studies have primarily addressed differences in behavior between primiparous and multiparous cows [66], but to our knowledge none has addressed behavioral changes during milking with continuous increasing age.…”
Section: Discussionmentioning
confidence: 99%